Parental supervision, children’s self-control and smartphone dependence in rural children: a qualitative comparative analysis from China - Li, Na; Liu, Wushuang; Yu, Suzhen; Yang, Rui (Frontiers in Psychology, 2025)
ObjectiveThis study explored the developmental pathways of smartphone dependence among rural children in China, focusing on the interplay between parental supervision, children’s self-control, and parent–child relationships.MethodsIn-depth interviews were conducted with 20 rural Chinese children and their parents. A Qualitative Comparative Analysis was employed to examine the conditions and mechanisms underlying smartphone dependence from both children’s and parents’ perspectives.ResultsThree distinct pathways to smartphone dependence were identified. Path 1: Children who were not left behind exhibited low self-control, lacked supervision and guidance, and had introverted personalities, and were more susceptible to smartphone dependence. Paths 2 and 3— Children who were left behind in rural areas and lack self-control were prone to developing smartphone dependence, regardless of whether they had a distant or harmonious parent–child relationship and an introverted or extroverted personality.ConclusionChildren’s self-control and parental supervision were critical factors influencing the participants’ smartphone dependence. The children’s sex, age, academic performance, parents’ smartphone use duration, and primary caregivers’ parenting skills moderated these influencing paths. Interventions should focus on enhancing children’s self-control through skill-building and equipping parents and primary caregivers with effective supervision, communication, and boundary-setting strategies to foster healthier technological habits.